The Rise of the Therapeutic State - Polsky, Andrew J. (Book collections on Project MUSE., 2001)
Assuming that "marginal" citizens cannot govern their own lives, proponents of the therapeutic state urge casework intervention to reshape the attitudes and behaviors of those who live outside the social mainstream. Thus the victims of poverty, delinquency, family violence, and other problems are to be "normalized." But "normalize," to Andrew Polsky, is a term that "jars the ear, as well it should when we consider what this effort is all about." Here he investigates the broad network of public agencies that adopt the casework approach.